2013
DOI: 10.1371/journal.pone.0067488
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Temporal Lobe Injury for Nasopharyngeal Carcinoma: A Comparison of Intensity-Modulated Radiotherapy and Conventional Two-Dimensional Radiotherapy

Abstract: BackgroundTo compare the radiation-induced temporal lobe injury (TLI) in patients with nasopharyngeal carcinoma (NPC) treated with intensity-modulated radiotherapy (IMRT) or two-dimensional conventional radiotherapy (2D-CRT).Patients and Methods1276 cases of NPC treated with IMRT or 2D-CRT were retrospectively reviewed. A diagnosis of TLI was made on follow-up magnetic resonance imaging (MRI).ResultsThe crude incidence of TLI was 7.5% and 10.8% (P = 0.048), and the actuarial 5-year incidence was 16% and 34.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 20 publications
2
71
2
Order By: Relevance
“…Of the 79 full articles retrieved, 38 were further excluded for no matched comparison, 19 for reviews, 12 for insufficient data, and 2 for repeated patients. Finally, 8 articles [6,[12][13][14][26][27][28][29] met the inclusion criteria and the flowchart of the retrieved studies are presented in Fig. 1.…”
Section: Search Results and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 79 full articles retrieved, 38 were further excluded for no matched comparison, 19 for reviews, 12 for insufficient data, and 2 for repeated patients. Finally, 8 articles [6,[12][13][14][26][27][28][29] met the inclusion criteria and the flowchart of the retrieved studies are presented in Fig. 1.…”
Section: Search Results and Characteristics Of Studiesmentioning
confidence: 99%
“…Many clinical studies have shown that IMRT was significantly better than conventional RT in terms of parotid sparing and improved QoL for NPC [11,12]. It is also reported increasingly that IMRT is able to reduce the rates of TLN compared with 2D-RT [13,14]. Despite the potential advantages of IMRT for NPC, it is still not clear if IMRT might be better than 2D-RT or 3D-CRT for patients with NPC.…”
Section: Introductionmentioning
confidence: 99%
“…This explanation is further endorsed by previous report of the association between the T stage of NPC and temporal lobe injury in IMRT patients, where a larger tumor extension indicated a compromise in planning dose for the temporal lobe. The reported incidence rate is between 4.8% to 16%, and may gradually increase over time after IMRT (4,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of dosimetric correlations with RAIC suggest that risk can be kept below 5% when doses of 63 Gy is delivered to small volumes of the brain (≤ 2cc), but increases towards 50% with doses of 70 Gy to 80 Gy (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%